Effect of combined air cooling and nano enhanced phase change materials on thermal management of lithium-ion batteries. (25th August 2022) - Anqi, Ali E.; Li, Changhe; Dhahad, Hayder A.; Sharma, Kamal; ATTIA, El-Awady; Abdelrahman, Anas; Mohammed, Azheen Ghafour; Alamri, Sagr; Rajhi, Ali A.
Abstract: The thermal management of a lithium-ion battery (LINB) cell in three dimensions was described in this study. For the thermal control of the LINB, two strategies were used: active and passive. For the passive heat management approach, phase change material (PCM) was employed. The LINB was put in a PCM-filled chamber. Two circular and oval chambers were placed around the LINB. In order to actively manage the heat, the LINB was thermally managed by placing the chamber and the LINB in an air duct. By changing the inlet air flow rate 0.1 cm/s to 0.4 cm/s, the temperature of the LINB, the amount of heat transfer coefficient (CHTR) and the volume fraction (VLF) of the PCM were investigated at different times (0 to 5000 s) for the two chamber shapes. Finite element method and COMSOL software were used for simulation. The results of this study showed that increasing the inlet air flow rate increases the CHTR of the LINB. Also, increasing the air speed caused the VLF of PCM to decrease. Over time, the CHTR increases and also over time, the LINB temperature increases. The hexagonal chamber resulted in a higher quantity of molten PCM than the circular chamber, particularly at t = 1200 s. Highlights: 3D investigation of the thermal management of a lithium-ion battery Utilizing active and passive strategies in the investigation Putting the battery in a PCM-filled chamber with two different shapes in passive strategy Obtaining temperature, CHTR and VLF of the PCM in different inlet air flow rate